STAGES OF FOOD BRAND FORMATION IN THE FOOD MARKET (Marketing Journal, 2025)
The formation of a national food brand plays a pivotal role in enhancing a country's competitiveness in the global food market while also contributing to the sustainable development of its agro -industrial sector. This paper explores the theoretical and met hodological foundations necessary for the creation of a national food brand, emphasizing the integration of economic, cultural, marketing, and policy - related components. Drawing on branding theories, consumer behavior studies, and value chain models, the r esearch establishes a comprehensive framework that aligns national identity with product differentiation strategies. The study also critically reviews international practices and benchmarks in food branding to extract adaptable methodologies relevant to na tional contexts. A particular focus is placed on the methodological tools needed to assess consumer perception, brand equity, and socio - economic impact. The paper concludes by proposing a structured approach to building and institutionalizing a national fo od brand that supports both local producers and international positioning, contributing to food security, rural development, and export diversification.
Keywords: marketing strategy; food brand; market; brand; methodological foundations; local brand